Screening Policy for Early Detection of Cervical Cancer - Nadhiroh, A’im Matun; Anifah, Fulatul; Rozifa, Annisa Wigati (Jurnal Kebidanan, 2025)
Cervical cancer is one of the leading causes of cancer-related deaths among women worldwide. Early detection through effective screening programs has been proven to reduce the incidence and mortality rates of cervical cancer. Objective: This study aims to analyze screening policies for early cervical cancer detection. Methods: A literature review from various references will be used. Results: The findings indicate that the primary screening techniques include cytology tests (Pap smear and liquid-based cytology), visual inspection (VIA and VILI), and HPV-DNA testing. Challenges in implementing screening programs include a lack of trained healthcare personnel, unequal access to services, and low adherence to follow-up for abnormal screening results, particularly in remote and low-income areas. Indonesia has adopted a national strategy aligned with WHO recommendations, encompassing health promotion, pre-cancer screening, appropriate referral pathways, standard facilities and equipment provision, and HPV vaccination policies. Conclusion: This study concludes that comprehensive guidelines are needed to regulate the organization and implementation of screening programs, including recommendations for target age groups, screening intervals, and a sustainable system for evaluation and monitoring to enhance the effectiveness of early cervical cancer detection.